Evidence mapping on barriers in accessing prenatal healthcare services among homeless women: a scoping review - Monsurat Adepeju Lateef; Julian David Pillay (BMC Health Services Research)
Abstract Introduction Prenatal care is crucial, but accessing healthcare services has been a challenge for pregnant homeless women in Africa. The majority in this marginalised group are not screened for common pregnancy complications such as preeclampsia, infection, and stillbirth. Therefore, this scoping review aims to explore the barriers to accessing prenatal healthcare services for pregnant homeless women in Africa. Methods This scoping review was conducted using the methodological framework developed by Arksey and O'Malley. Four electronic databases: CINHAL complete, Scopus, PubMed and Web of Science were searched. In addition, a manual search was done on Google Scholar and other websites for grey literature. The search was confined to 20 years (2004 to 2024). The reference lists of the articles searched and included in the study were examined for additional titles that satisfied the inclusion criteria. Results Out of 3910 titles screened, only three (n = 3) studies met the eligibility inclusion criteria in this study. Two out of the three studies that were included were conducted in Ethiopia while one was conducted in South Africa. All of the studies used qualitative research methods. Across the 3 studies, the ages of the participants ranged from 15 to 45 years. Two major themes were identified, namely: Theme 1: the barrier to accessing prenatal healthcare services and Theme 2: Social Support needs. Theme 1 has four categories that emerged: lack of awareness; fear of stigma and discrimination; previous negative experiences; and financial constraints. Theme 2 emerged with two categories: psychological and emotional needs; and nutritional needs during pregnancy. Conclusion This study identified barriers and facilitators to access prenatal healthcare services among pregnant homeless women as a multifaceted issue, rooted in stigma and discrimination, lack of awareness, and negative experiences with healthcare providers. There is a need for interventions to improve access, health and well-being for this marginalised group—from the government, stakeholders, and nongovernmental organisations.